Morphologic changes of the nasal cavity induced by rapid maxillary expansion: A study on 3-dimensional computed tomography models - ACAR, ZEYNEP AHÜ (MOSBY-ELSEVIER, 2009)
Introduction: The aim of this study was to evaluate the effect of rapid maxillary expansion on the volume of the nasal cavity by using computed tomography. Methods: The sample consisted of 24 patients (10 boys, 14 girls) in the permanent dentition who had maxillary constriction and bilateral posterior crossbite. Ten patients had skeletal Class I and 14 had Class II relationships. Skeletal maturity was assessed with the modified cervical vertebral maturation method. Computed tomograms were taken before expansion and at the end of the 3-month retention period, after active expansion. The tomograms were analyzed by Mimics software (version 10.11, Materialise Medical Co, Leuven, Belgium) to reconstruct 3-dimensional images and calculate the volume of the nasal cavities before and after expansion. Results and Conclusions: A significant (P = 0.000) average increase of 11.3% in nasal volume was found. Sex, growth, and skeletal relationship did not influence measurements or response to treatment. A significant difference was found in the volume increase between the Class I and Class II patients, but it was attributed to the longer expansion period of the latter. Therefore, rapid maxillary expansion induces a significant average increase of the nasal volume and consequently can increase nasal permeability and establish a predominant nasal respiration pattern. (Am J Orthod Dentofacial Orthop 2009;136:815-21)
Keywords: ACOUSTIC RHINOMETRY; PALATAL EXPANSION; AIRWAY-RESISTANCE; DENTAL CHANGES; SKELETAL; DIMENSIONS; GEOMETRY; GROWTH; VOLUME